Some thoughts on the relations between the tax crime and money laundering crime in the Peruvian Criminal Law (2015)
In the following article we analyse the possibility of the existence of a concurrence of crimes between tax evasion and money laundering in peruvian criminal law. In this respect, in contrast to the opinion that defend the viability of the aforementioned